A study of eco-culture-tourism coupling and coordinated development and influencing mechanism in the Yellow River Basin based on spatial production theory - Mengyin Wang; Xiaotian Wang (Ecological Indicators)
The effective synergistic interaction among ecology, culture, and tourism in the Yellow River Basin significantly contributes to the realization of regional coordination and high-quality development. Based on the spatial production theory, this paper applies the coupling coordination model to deeply explore the spatio-temporal development evolution and coupling coordination development of the three systems of ecology, culture and tourism in the nine provinces (autonomous regions) of the Yellow River Basin from 2011 to 2023. Moreover, the obstacle degree model is used to explore the obstacle factors restricting the coupled and coordinated development of the three, and the driving factors are explored based on geographic detector. The results show that: the average value of the comprehensive benefits of the three systems is ecology (0.441) > culture (0.297) > tourism (0.282); the overall coupled and coordinated development of the composite system is slowly rising, yet remains at a relatively low level, with most regions categorized as mild disorder or on the verge of disorder; the spatial regional gradient is significantly differentiated, showing a “downstream > middle reaches > upstream” coordinated development characteristic. The coordinated development of ecology, culture and tourism is driven by the combined effects of internal factors (ecological environment, cultural industry resources, and tourism industry scale), and external factors (government, facilities, economic and geographical factors). Therefore, there is a mutually reinforcing relationship among the ecological, cultural, and tourism resources in the Yellow River Basin. The optimal utilization and complementarity of resources can be achieved through coordinated development, thus promoting the economic development and sustainability of the region.